Kalindaqdaq Tradition of Mandar Community in West Sulawesi: Islamic Education Study Based on Local Wisdom - Ridhwan, Ridhwan; Samad, Sri Astuti A.; Kiramang, Khaeruddin; Hasan, Hasan (el Harakah: Jurnal Budaya Islam, 2021)
Kalindaqdaq is a literary work of Mandar community which is considered as an old poetry and one of the actualizations of religion and local wisdom harmonization. Several studies on Kalindaqdaq have been conducted but none explores from ethno-pedagogical perspective. This study is aimed at supporting the importance of local wisdom in Islamic education because the education process cannot be separated from the expression of culture and customary orders proven to be capable of educating humans.  This study employs a qualitative method with ethno pedagogical approach. The data are collected through a library research by identifying, selecting, and reviewing research outputs relevant to the topic and literary works about Kalindaqdaq. The analysis is conducted by finding out the integration or interconnection relationships of the local wisdom with education. The findings reveal that Kalindaqdaq functions as a means of religious education, morals, traditional socialization media, communication tools for traditional narratives and entertainment. Kalindaqdaq as a cultural product contains Islamic educational values, such as monotheism, worship, morals, social and heroism. The implication of this study derives from the findings. The findings imply that kalindaqdaq is important under an ethnopedagogical perspective, applicable in the educational process. This study is the evidence of Islam and local wisdom harmonization, which highly supports the development of Islamic education as an integral part of education in Indonesia. Kalindaqdaq merupakan karya sastra masyarakat Mandar yang tergolong sebagai puisi lama dan dianggap sebagai salah satu aktualisasi harmonisasi agama dan kearifan lokal. Beberapa penelitian tentang Kalindaqdaq telah dilakukan tetapi belum ada yang mengeksplorasi harmonisasi pendidikan Islam dan kearifan lokal dengan perspektif etnopedagogis. Penelitian ini menggunakan metode kualitatif dengan pendekatan etnopedagogis. Signifikansi kajian ini adalah untuk menegaskan bahwa keberadaan kearifan lokal dalam pendidikan Islam menjadi penting karena proses pendidikan tidak lepas dari ekspresi budaya dan tatanan adat yang dapat mendidik manusia. Pengumpulan data dilakukan melalui studi pustaka dengan mengidentifikasi, memilih, dan mengkaji literature ilmiah yang relevan dengan topik penelitian dan karya sastra tentang Kalindaqdaq. Analisis dilakukan untuk mengetahui keterpaduan atau keterkaitan kearifan lokal dengan pendidikan. Temuan mengungkapkan bahwa Kalindaqdaq memiliki fungsi sebagai sarana pendidikan agama, moral, media sosialisasi tradisional, alat komunikasi untuk narasi tradisional dan hiburan. Kalindaqdaq sebagai produk budaya mengandung nilai-nilai pendidikan Islam seperti tauhid, ibadah, akhlak, sosial dan kepahlawanan. Implikasi dari penelitian ini berasal dari temuan. Temuan ini menyiratkan bahwa kalindaqdaq penting dari perspektif etnopedagogis, yaitu penggunaan kearifan lokal dalam proses pendidikan. Kajian ini merupakan bukti harmonisasi dan adat Islam serta mendukung pengembangan pendidikan Islam sebagai bagian integral dari pendidikan di Indonesia.